2009
DOI: 10.1021/la9006229
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Shell/Oil-Core Microcapsules with Controlled Shell Thickness and Their Breakage Stress

Abstract: The encapsulation of one material by another, to form core-shell particles (microcapsules), has many applications, principally the containment, protection, and distribution of an active material. This work describes the development of core-shell particles with silicone oil cores and solid silica-like shells of controlled thickness. Oligomeric polydimethylsiloxane (PDMS) emulsions are employed as the core templates for the formation of the solid shells. The core templates are prepared by the surfactant-free, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 14 publications
5
52
0
Order By: Relevance
“…Because of the ionization of -NH 2 , the concentration of OH À in water layer near the interface increases, resulting in a suitable pH value for hydrolysis and polycondensation of the silicon precursors. Analogous to the phenomena reported in previous studies [53][54][55], the amount of APTS concentration in the bicomponent precursors is important for the formation of the silica shell. When the ratio of TEOS to APTS is 20 mL:5 mL, particles with regular sphere shape can be obtained (Fig.…”
Section: Preparation Of Tris@sio 2 Capsulessupporting
confidence: 71%
“…Because of the ionization of -NH 2 , the concentration of OH À in water layer near the interface increases, resulting in a suitable pH value for hydrolysis and polycondensation of the silicon precursors. Analogous to the phenomena reported in previous studies [53][54][55], the amount of APTS concentration in the bicomponent precursors is important for the formation of the silica shell. When the ratio of TEOS to APTS is 20 mL:5 mL, particles with regular sphere shape can be obtained (Fig.…”
Section: Preparation Of Tris@sio 2 Capsulessupporting
confidence: 71%
“…This is straightforward when the continuous phase is aqueous, where, in principle, the interfacial condensation reaction should continue until all the added monomer is reacted. Hence, as the current authors have shown [1], relatively thick silica shells may be formed (although if the concentration of monomer initially is too high, secondary condensation reactions may occur, producing silica particles in solution). However, if the continuous phase is oil, and the dispersed phase is the aqueous one, then the monomer and water molecules have to react across the interface to produce the solid shell.…”
Section: Introductionmentioning
confidence: 60%
“…Under basic or acidic conditions an interfacial condensation reaction occurs at the PDMS/water interface, leading to silica-based shells up to $0.1 lm in thickness. A linear correlation was found [1] between the breakage force of the shells and their thickness. Also, it was found [1] that dye molecules could be solubilised into the PDMS liquid cores, prior to shell formation, and that the dye did not leak out into the continuous phase from the microcapsules dispersed in water.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations